Localization of fluorescein-labeled antinucleoside antibodies in glomeruli of patients with active systemic lupus erythematosus nephritis - Andres, G. A. (1970)
Renal tissues from two groups of patients were studied with fluorescein-labeled (Fl-) antibodies (Abs) to immunoglobulins, complement, and antibodies prepared in rabbits against BSA conjugate of 5-methyluridine (T) and cytidine (C), the latter two of which react specifically with denatured DNA. The first group consisted of 13 SLE patients, and the second consisted of 53 patients with non-SLE nephropathies. The data obtained from the two groups of patients were used for comparison, and they showed the following: (a) Fl-Abs to immunoglobulins and complement were bound in the glomeruli of tissues from all patients with active SLE glomerulonephritis characterized by deposits of foreign material in glomerular capillary walls (GCW). The fluorescent pattern was granular, corresponding to the distribution of the glomerular deposits, as seen by electron microscopy. Fl-Abs reactive with thymine and cytosine were bound in the GCW of eight of the nine patients with active SLE glomerulonephritis and showed the same granular distribution. The capacity of these latter Fl-Abs to stain the GCW was removed by absorption with the homologous antigen or denatured DNA. (b) Fl-Abs to immunoglobulins, complement, and pyrimidine bases of DNA did not react with the GCW of two SLE patients without clinical and histologic evidence of glomerulonephritis or with the sclerotic glomeruli of two uremic patients with chronic “burned out” lupus nephritis. (c) The glomeruli of 47 of the 53 patients with other nephropathies bound Fl-Abs to immunoglobulins and complement to some extent, and in 26, the localization appeared as marked as in the patients with active SLE glomerulonephritis. Fl-Abs reactive with thymine and cytosine were bound in the GCW of only one of the renal tissues from the 53 non-SLE patients. In the remaining 52, no binding was seen. (d) The findings are consistent with the hypothesis that antigen-antibody complexes, formed by denatured DNA, specific antibody, and complement, are present in the deposits of foreign material accumulated in the GCW of patients with active SLE glomerulonephritis, and that they may contribute to the pathogenesis of this renal disease.